(untitled) (Revista Contexto & Saúde, 2024)
Purpose: Investigate the impact of the Covid-19 pandemic on the higher education through the perception of Brazilian undergraduates. Methods: A cross-sectional study was conducted with 1006 students of public and private universities. Data collection happened between September-December 2020 with an online questionnaire addressing socioeconomic characteristics, use of anxiolytics/antidepressants and issues related to the course. Data were analyzed using Poisson regression (α = 5%). Results: Most students (68.7%) perceived an impact on their education and reported a high satisfaction with the course (62.2%). Age (OR = 0.98, 95%CI: 0.96 – 0.99), residing in the northern region of the country (OR= 1.26, 95%CI: 1.06 – 1.50), enrollment at a public university (OR= 1.28, 95%CI: 1.17 – 1.40) and lower satisfaction with the course (OR= 1.13, 95%CI: 1.04 – 1.23) were associated with the perception of impact. Regarding self-rated performance in the courses, 41.7% students reported a very low/low performance. A family income of up to two times the monthly minimum wage (OR= 0.68, 95% CI: 0.48 – 0.97), residing in the northeastern region of the country (OR= 0.68, 95% CI: 0.48 – 0.97) and lower satisfaction with the course (OR= 0.36, 95% CI: 0.23 – 0.53) were associated with this outcome. Conclusions: The pandemic negatively affected two thirds of undergraduates, especially the younger, from the northern region, public universities and those less satisfied with the course. Nearly forty percent of students rated their academic performance during the pandemic as very low/low, especially those with a low family income, from the northeastern region and those less satisfied with the course.